How buyer relationship influences value co-creation: The moderating role of personality traits - Omar N.A.; Kassim A.S.; Mohd-Ramly S.; Nazri M.A.; Alam S.S.; Che Senik Z. (Society for Alliance, Fidelity and Advancement (SAFA), 2024)
Indexed by Scopus/ERA